2015
DOI: 10.1111/1471-0528.13394
|View full text |Cite
|
Sign up to set email alerts
|

Uterine rupture: trends over 40 years

Abstract: Objective To follow trends of uterine rupture over a period of 40 years in Norway.Design Population-based study using data from the Medical Birth Registry, the Patient Administration System, and medical records.Setting Norway.Sample Women giving birth in 21 maternity units in Norway during the period 1967-2008 (n = 1 441 712 maternities).Methods The incidence and outcomes of uterine rupture were compared across four decades : 1967-1977; 1978-1988; 1989-1999; and 2000-2008. Multivariable logistic regression wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
71
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(83 citation statements)
references
References 25 publications
(29 reference statements)
7
71
3
Order By: Relevance
“…First, we may have missed additional ruptures that were not recorded in the MBRN because only 21 units were included in the PAS search, as mentioned in the Material and methods section. However, we found that the results were similar regarding risk factors for different maternal outcomes following complete uterine ruptures in both the previously fully validated sample of 163 ruptures and in our current larger sample of 247, which was partially validated. Therefore, we concluded that potentially misdiagnosed cases did not influence the study results.…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…First, we may have missed additional ruptures that were not recorded in the MBRN because only 21 units were included in the PAS search, as mentioned in the Material and methods section. However, we found that the results were similar regarding risk factors for different maternal outcomes following complete uterine ruptures in both the previously fully validated sample of 163 ruptures and in our current larger sample of 247, which was partially validated. Therefore, we concluded that potentially misdiagnosed cases did not influence the study results.…”
Section: Discussionsupporting
confidence: 69%
“…This was a retrospective population‐based study including rupture cases identified in the whole pregnant population in Norway in 1967‐2008. In our two earlier papers on trends and risk factors for complete uterine ruptures, we included a validated population from 22 of the 48 maternity units in Norway, between 1967 and 2008 . In the current study we included the whole pregnant population of all 48 units, thus enlarging the sample of complete uterine ruptures.…”
Section: Methodsmentioning
confidence: 99%
“…A study from the United States reported rupture of the unscarred uterus in 4.54 per 100,000 deliveries or about 1 in 22,000 deliveries [10]. The incidence of rupture in both scarred and unscarred uteri has increased during recent decades [12]. …”
Section: Discussionmentioning
confidence: 99%
“…The risk of uterine rupture is much lower in unscarred uterus than scarred one. Regarding its incidence, different rates were mentioned in various articles (13). The mean rate is 0.009% in a period of 20 years (14).…”
Section: Introductionmentioning
confidence: 99%